Obviate SLA violation for Resource Allocation based on SaaS in Cloud Environment - Khatri, Faraz; Shaikh, Faraz; Yadav, Deepak; Murkute, Pramod (International Journal of Computer Sciences and Engineering, 2015)
Cloud Computing is an emerging way of storing data, but still it on the verge of improving with every development. Taken in an account for performing more profit, as providing services to various users are difficult because it should in a manner though all can benefit in their work. Allocation is tedious task due to: 1) Diversity in resource allocation. 2) Hard to map request 3) frequent change in customer. Cloud level of agreement done throughout the Service Provided, SLA provide a standard way of controlling the mechanism. This paper deal with an allocation of resource considering a token like price, response time, space and contract length. As all the type of user can benefit the more of the system resource.